THE COMPARATIVE STUDY OF EMPLOYEE PERFORMANCE BEFORE AND AFTER TRAINING AT BANK RAKYAT INDONESIA, MANADO SARAPUNG BRANCH - Mamahit, Cindy (Sam Ratulangi University, 2016)
Employee performance important for the company, and the company should have training program for all employees to improve and develop the employee performance indicator that exist within them. The main purpose of this research is to analyze the significant difference in employee performance before and after training at Bank Rakyat Indonesia, Manado Sarapung branch that is measured by variable which used in this research such as: Knowledge, skill, teamwork/cooperation, communication, ability, and standards. This study is going to use Comparative means Paired Sample t-test (Dependent variable) to achieve the main purpose of this research. The number of respondents are 100 employees take from the employees at Bank Rakyat Indonesia, Manado Sarapung branch who already follow the training. The result of this study shows that employees at Bank Rakyat Indonesia, Manado Sarapung branch have a significant different of employee performance before and after training. Therefore, The management especially Human Resource Department Bank Rakyat Indonesia (Manado Sarapung Branch) should improve their training programs especially on technical knowledge, cooperation, and communication skills for self-development of the employees at Bank Rakyat Indonesia, Manado branch Sarapung.